On epithets qua attributive anaphors. - Corazza, Eros (Journal of Linguistics, 2005)
A multiple-proposition theory is proposed, according to which a single utterance can express several distinct propositions. An utterance of "Jon, the idiot, missed the train" expresses the official proposition THAT JON MISSED THE TRAIN and the background proposition THAT JON IS AN IDIOT. It is argued that only the official proposition affects the truth-value of the utterance, while the background proposition(s) may be treated similarly to pragmatic presuppositions. The multiple-proposition theory helps us to defend the thesis that, in an utterance such as "Jon promised to come but the idiot missed the train", the epithet the idiot must be understood as an attributive anaphor, for it inherits its value from Jon and attributes to Jon the property of being an idiot. It is argued that epithets in such constructions should be viewed in a way similar to quasi-indicators, insofar as the latter are also attributive anaphors. The quasi-indicator she herself in "Jane believes that she (herself) is rich" inherits its value from Jane and attributes an I-thought to Jane. In focusing on the similarities and differences between epithets and quasi-indicators, we can explain some alleged difficulties, difficulties which suggest that epithets cannot. be anaphoric (e.g. "*Jon claimed/said/thinks... that the bastard was honest"). It is shown that the ungrammaticality of sentences like these rests on the fact that the epithet is embedded in what should be a de se attribution (e.g. "Jon claimed/said/ thinks that he (himself) was honest") while its nature is to contribute to the expression of a de re attribution. This helps us to understand the ungrammaticality of " Jane said/thinks/promised/ ... that the idiot will come" vs. the grammaticality of "Jane said/thinks/promised/ ... that she (herself) will come" on the one hand, and, on the other hand, the ungrammaticality of "Jon ran over a man who was trying to give him (*himself)i directions" vs. the grammaticality of "Jon ran over a man who was trying to give the idiot directions".